Development of method of multifactor classification of transport and logistic processes - Bosov, Arkadii; Khalipova, Nataliya; Prohoniuk, Iryna; Kuzmenko, Violetta; Duhanets, Viktor; Shevchenko, Inna (Eastern-European Journal of Enterprise Technologies, 2018)
A method of classification of a set of objects and/or processes in transport and logistics systems on the basis of a multifactor analysis was proposed. Combination of the methods of statistical and factor analysis, the systems hierarchy analysis method and modern methods of logistic analysis has enabled formation of a complex classification model. A three-stage algorithm was proposed for solving multifactor problems of classification in the fields of transport and logistics and the theory of organization of cargo transportation. At the first stage, the factor influence is investigated based on the chosen criterion. At the second stage, a comprehensive analytical indicator is created that characterizes the influence of factors on the objects under study and is based on the systemic hierarchy analysis method. The use of the hierarchy analysis method enables both use of factual data based on a thorough statistical analysis and involvement of experts in solving multifactorial decision-making problems. The use of modern logistic analysis methods in the third stage makes it possible to reasonably divide classification objects in the transport and logistics systems among various numbers of dynamic classes. At this stage, it is also possible to involve experts in the formation of boundaries of classes. The model was implemented using the Symbolic Computing Package in the Maple-7 and the Microsoft Excel environments. Classification of Ukraine's trading partner countries by indicators of international turnover of certain groups of goods which can be transported in universal containers according to the Ukrainian foreign economic activity classifier (UFEAC) was made. Through simulation, the set of partner countries in foreign trade was divided into three classes. Classification of Ukraine’s partner countries by indicators of international turnover of certain groups of goods which can be transported in universal containers in accordance with the Ukraine’s foreign economic activity classifier (UFEAC) has allowed us to divide a set of partner countries in foreign trade into three classes. The classification results are in good agreement with the classic ABC analysis. Classification of countries by the criterion of specific value of goods flows has allowed us to divide the set of countries under study into two classes. This is explained by the fact that classification was made for a set of all partner countries in the first example and twenty countries with the largest turnover were previously selected in the second example. Application of the proposed method of multifactor classification ensures dividing the objects of classification, in general, among different numbers of groups. At the same time, the boundaries of dynamic classes which are formed on the basis of a comprehensive assessment of the factor influence and depend on the concrete formulation of the problem and the criteria taken into account. The proposed classification method can be used in transport, logistics, customs and brokerage enterprises, as it allows for planning and controlling supply of goods to varying degrees of detail and apply appropriate strategies. Further development and improvement of this study is possible in the direction of using intelligent systems and algorithms to solve problems of multifactor analysis of transport and logistics systems.